The Difference of Forced Vital Capacity Ratio (%FVC) between Junior High School Students Living in High Altitude and Low Altitude - Kurniawan, Fery Ardi; Suselo, Yuliana Heri; Randita, Amandha Boy Timor (Nexus Biomedika, 2015)
Background: Environment will affect the condition and bodyâs ability to adapt. The difference of characteristics and environmental conditions between high altitude and low altitude causes the adaptation of body, in order to work normally. This adaptation causes change in many organ systems including the respiratory system. Forced Vital Capacity Ratio (%FVC) is the ratio between Forced Vital Capacity (FVC) and predicted value of vital capacity. FVC is influenced by lungâs ability to compliance and recoil. The limitations on these ability will reduce the ability to inspire the air so it will be difficult to get oxygen. This research aimed to analyze the difference of %FVC between junior high school students living in high altitude and low altitude. Methods:This research was a cross-sectional observational analytic. The subjects were 30 male students of SMP Amal Mulya Tawangmangu Karanganyar (altitude 966 meters) and 30 male students of SMP Negeri 2 Kretek Bantul (altitude 15 meters). The subjects were selected by using non random purposive sampling and met the inclusion and exclusion criteria. Data of %FVC were measured by Minato AutoSpiro AS.300 Spirometry. The data were analyzed using Independent t-test with significance level Î± = 95%. Results: Mean of %FVC of junior high school students in high altitude was 77.67 Â± 8.806 whereas mean of that in low altitude was 76.38 Â± 8.493 withÂ p = 0.564. Conclusions: There is no significant difference of %FVC between junior high school students living in high altitude and low altitude. Keywords: Forced Vital Capacity Ratio (%FVC), high altitude, low altitude, spirometry